2008
DOI: 10.1002/ebch.269
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane review: Selective serotonin reuptake inhibitors (SSRIs) for depressive disorders in children and adolescents

Abstract: BackgroundDepressive disorders are common in young people and are associated with significant negative impacts. Selective serotonin reuptake inhibitors (SSRIs) are often used, however, evidence of their effectiveness in children and adolescents is not clear. Furthermore, there have been warnings against their use in this population due to concerns about increased risk of suicidal ideation and behaviour.ObjectivesTo determine the efficacy and adverse outcomes, including definitive suicidal behaviour and suicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 111 publications
1
11
0
Order By: Relevance
“…Interpretation of efficacy results in clinical trials of antidepressants is further complicated by a significantly (p = 0.002) higher placebo response rate in paediatric patients with MDD (49.6%) than those with obsessive compulsive disorder (31.0%) or other anxiety disorders (39.6%). [8] Despite these difficulties and a general lack of evidence for the clinical efficacy of antidepressant treatment (with the exception of the SSRI fluoxetine) in children and adolescents, [9,10] the consensus of treatment guidelines [2,11,12] is that antidepressant therapy is needed in some paediatric patients with MDD, particularly those with moderate to severe disease.…”
mentioning
confidence: 99%
“…Interpretation of efficacy results in clinical trials of antidepressants is further complicated by a significantly (p = 0.002) higher placebo response rate in paediatric patients with MDD (49.6%) than those with obsessive compulsive disorder (31.0%) or other anxiety disorders (39.6%). [8] Despite these difficulties and a general lack of evidence for the clinical efficacy of antidepressant treatment (with the exception of the SSRI fluoxetine) in children and adolescents, [9,10] the consensus of treatment guidelines [2,11,12] is that antidepressant therapy is needed in some paediatric patients with MDD, particularly those with moderate to severe disease.…”
mentioning
confidence: 99%
“…The majority of guidelines on the treatment of depressive disorders in young people recommend the judicious use of medication, specifically selective serotonin reuptake inhibitors (SSRIs), in the context of careful monitoring of symptoms and side effects (AACAP 2007;Cheung 2008a;NICE 2005;Zuckerbrot 2007). The SSRI for which there is the most consistent evidence of a statistically significant reduction in depressive symptoms compared with placebo is fluoxetine (Hetrick 2007;Richmond 2005;Whittington 2004). The Committee on the Safety of Medicines (CSM) (CSM 2004) and the Food and Drug Administration (FDA) (FDA 2004) recommend it as the preferred SSRI for use in young people, and the National Institute for Health and Clinical Excellence (NICE) guidelines state specifically that fluoxetine should be the first antidepressant medication option (NICE 2005).…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…A number of randomised controlled trials (RCTs) are available to guide treatment decisions for adult depressive disorder, but the evidence-base for the treatment of child and adolescent depressive disorder is much less established. Nevertheless, an increasing number of RCTs of psychological interventions and antidepressant medications are being undertaken in this population, and several Cochrane reviews of treatments for depressive disorders in children and adolescents are already available or underway (Hazell 2002;Hetrick 2007;Watanabe 2004). Findings from RCTs have suggested that some psychological therapies might be more effective than a variety of control comparators.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…The DDD was assumed to be the dose for liquid dose forms. The basis of this assumption was that there is a range of different drug strengths available in Finland, thereby negating the need for dividing tablets or capsules, and that the recommended daily dose of SSRI treatment is similar for children, adolescents, and adults [13,30]. The discontinuation date was based on the period covered by the last prescription.…”
Section: Measures and Definitionsmentioning
confidence: 99%